The Efforts to Maintain Dental Health During Covid-19 Pandemic by Mothers of Children with Autism Spectrum Disorder - Wahyudi, Irene Anastasia; Tedjosasongko, Udijanto; Dewi, Ardianti Maartrina (Indonesian Journal of Dental Medicine, 2023)
Children with autism spectrum disorder (ASD) have special characteristics and problems, including oral health problems. The Covid19  pandemic condition requires adjustment in many ways. The information about the efforts of parents, especially mothers in maintaining the oral health of their ASD children isneeded so that assistance can be provided efficiently and effectively. Purpose: to determine the mother's efforts in maintaining the dental health of children with ASD during the COVID-19 pandemic. Method: A questionnaire was given to 109 mothers who have ASD children from the Mutiara Hati Autism Foundation in Surabaya City and Mojokerto City, then the data were analyzed using descriptive analysis. Results: It was found that the majority of mothers did not bring their children to the dentist during pandemic, so the problem of dental caries had not been treated optimally. Mothers' efforts in maintaining the dental health of their ASD children during the COVID-19 pandemic were; always accompanying the child to brush his teeth, and providing painkillers when the child has a toothache. The mothers did not know that there was an online dental consultation so they did not take advantage of it. Conclusion: The mother's efforts in maintaining the dental health of ASD children during the COVID-19 pandemic more limited, due to lack of knowledge in the prevention/treatment of dental disease; and concerns about virus transmission during dental treatment; and the lack of socialization of the use of online media for consultation with dentists.